Correction: The Molecular Mechanisms of the Antibacterial Effect of Picosecond Laser Generated Silver Nanoparticles and Their Toxicity to Human Cells. - Peri Korshed; Lin Li; Zhu Liu; Tao Wang (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0160078.].